PERAN ORANGTUA DALAM MENINGKATKAN PENDIDIKAN KARAKTER ANAK USIA DINI DALAM KELUARGA - Edi Widianto (Universitas Trunojoyo Madura, 2015)
The Role of Parents in Improving The Character of Early Childhood Education in The Family. Parents play an important role to develop their potential. parents are educators first and foremost in a family environment, parents need to be aware that the child has great potential at birth. The importance of early childhood education because of the period of child development goes more rapidly. At that time was the right time to lay the foundations of character education in accordance with its development. To achieve this, the required maximum effort from parents to educate children in all aspects of development and enhancing the role of parents as educators in the family. This study aimed to describe the role of parents in improving the character education in early childhood in the family. Research design used in this study is qualitative. the results of this study indicate that: 1) The value-character value given by parents to children in a family environment, among others: parents exercise self-discipline in children, train perseverance, responsible from an early age, an attitude of humility toward others, cultivate governance manners, uphold the values of honesty, love of God with worship familiarize timely; 2) The role of parents in transmitting the character education of children despite not run optimally, but parents continue to strive to improve it; 3) Barriers experienced by parents in implementing character education in the family is heavily influenced by factors outside the home environment.